NEUROPATHY SYMPTOM SCORE (NSS) AND E-SKIN DIABETIC SIMPLE TEST (E-SDST) AS A DIAGNOSTIC SCORE FOR DIABETIC NEUROPATHY - Sholichin, Sholichin; S, Syahrun; Sukmana, Mayusef; Samsugito, Iwan; Metungku, Fanny; Retnaningrum, Yuliana Rahma (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Diabetic neuropathy (ND) is experienced by more than 50% of people with diabetes and can lead to ulcers and even amputations if not detected early. Fast, accurate, and affordable detection is needed, especially in health facilities with limited equipment, to prevent serious complications due to nerve damage. Objective: The aim of this study was to assess the inter-rater reliability and validity of the Neuropathy Symptom Score (NSS) and the E-Skin Diabetic Simple Test (ESDST) as clinical diagnostic scores for diabetic neuropathy. Methods: The research design used was cross-sectional involving 176 respondents. The selected samples were then assessed for Neuropathy Symptom Score (NSS) and E-Skin Diabetic Simple Test (E-SDST) by two examiners at different times and places. The data obtained were categorized into positive diabetic neuropathy and negative neuropathy. Statistical analysis for reliability testing between examiners with Cohen's Kappa coefficient, while validity with a 2x2 table Results: The reliability value is obtained κ=0.68 with an alpha of 0.00 which means substantial agreement that there is agreement in using this tool from both raters. The results of ESDST validity compared to NSS obtained sensitivity results of 80.1% (high) and specificity 83.3% (high). Conclusion: E-SDST is able to screen people with ND is also capable as a specific diagnostic tool and as a clinical diagnostic tool diabetic neuropathy has moderate/sufficient inter-rater reliability.